2015
DOI: 10.1103/physreve.91.032141
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic geometry of supercooled water

Abstract: The thermodynamic curvature scalar R is evaluated for supercooled water with a two-state equation of state correlated with the most recent available experimental data. This model assumes a liquid-liquid critical point. Our investigation extends the understanding of the thermodynamic behavior of R considerably. We show that R diverges to -∞ when approaching the assumed liquid-liquid critical point. This limit is consistent with all of the fluid critical point models known so far. In addition, we demonstrate a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In our present study, the geometric structure of the ST2 model for supercooled water is analyzed based on the TSEOS developed by Holten et al [54], which models well the properties of real water [7,31]. Two versions of the TSEOS have been developed [54], a mean-field (MF) description and a so-called crossover (CO) approach, accounting for critical order-parameter fluctuations.…”
Section: Two-state Thermodynamics Of Watermentioning
confidence: 99%
See 2 more Smart Citations
“…In our present study, the geometric structure of the ST2 model for supercooled water is analyzed based on the TSEOS developed by Holten et al [54], which models well the properties of real water [7,31]. Two versions of the TSEOS have been developed [54], a mean-field (MF) description and a so-called crossover (CO) approach, accounting for critical order-parameter fluctuations.…”
Section: Two-state Thermodynamics Of Watermentioning
confidence: 99%
“…We recently extended these geometric ideas into the metastable water regime [7]. By applying a two-state equation of state (TSEOS), developed by Holten et al [31], a dramatically decreasing R, to −∞ at the postulated LLCP, was found on cooling into the metastable liquid state [7]. On the LDL side of the LLPT line, organized ice-like structures led to positive R, whereas the HDL side shows only negative R. Positive R in the LDL state appeared because tetragonal ice-like structures generally take up more space than the more disorganized HDL states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) and Eqs. (17)(18)(19)(20)(21)(22)(23). The black curves are based on lattice data with the condition n S = n Q = 0 (or equivalent for the isospin symmetric limit), whereas the red ones are for n S = 0 and n Q /n B = 0.4.…”
Section: Thermodynamic Geometry Of Qcdmentioning
confidence: 99%
“…Riemannian geometric theory of thermodynamics and statistical mechanics is nowadays successfully applied in diverse research areas [1][2][3][4][5][6][7][8][9]. At the beginning, these applications are limited to simple and well-known spin models.…”
Section: Introductionmentioning
confidence: 99%